Análisis de fallas de espárragos de carcaza de bomba de agua - Iorio, Antonio F.; Crespi, Juan C. (Comisión Nacional de Energía Atómica; Argentina, 1979)
Fil: Iorio, Antonio F. Comisión Nacional de Energía Atómica; Argentina